Effect of weed control and irrigation regimes on transplanted rice (Oryza sativa) in Kashmir valley - BALI, AMARJIT S; SHAH, M H; BALI, A S; HASSAN, B; SINGH, K N; KANTH, RAIHANA HABIB (The Indian Journal of Agricultural Sciences, 2013)
A fidd experiment was conducted during rainy season of 1993 and 1994 on silty clay-loam soil of Shalimar in Kashmir to study the effect of weed-control practices and irrigation regimes on weed-control efficiency and grain yield of transplanted rice (Oryza sativa L.). Among various weed-control treatments, weed-free treatment gave the highest wced-control efficiency and thereby resulted in the highest mean grain yield (6.32 tonnes/ha). It was 9.2, 70.8 and 77.5% more than that from the application of butachlor@ 1.5 kg a i/ba + 1 hand-weeding, 2,4 - D (ethyl ester of 2, 4 dichlorophenoxy acetic acid) @ 1.0 kg ai/ha + 1 hand-weeding and uuweeded control respectively. Weed-control efficiency and water- expense efficiency followed a trend identical to grain yield. However, application of butachlor @ 1.5 kg ai/ba + 1 hand-weeding proved more profitable, with highest benetit : cost ratio (1.50). Different irrigation regimes did not cause variation in the dry weight of weeds and weed-control efficiency. However, delayed irrigation supressed the broad-leaf weeds than continuous standing water (5 cm Â± irrigation at interval of 2 days). Continuous standing water and application of irrigation 2 days after infiltration of ponded water with mean benefit: cost ratio of 1.34 and 1.23 respectively recorded similar grain yield but significantly higher than irrigation at intervals of4 and 6 days, which in turn had higher mean water-expense efficiency. Â